Association of IGF‐1 gene rs2195239 polymorphism with the risk and clinical features of gastric cancer in a Chinese Han population. Issue 7 (9th March 2020) - Wang, Pengli; Zhou, Xiaoyan
Abstract: Background: Recently, a Japanese study investigated the relationship between insulin‐like growth factor‐1 (IGF‐1) gene rs2195239 polymorphism and gastric cancer (GC) risk and found rs2195239 polymorphism did not relate with the risk of GC. However, no Chinese studies have addressed this relationship until now. Thus, the aims of this study were to demonstrate whether IGF‐1 gene rs2195239 polymorphism was linked with the risk and clinical features of GC in a Chinese Han population. Methods: In order to verify the link between IGF‐1 gene rs2195239 polymorphism and GC risk, we recruited 361 GC cases and 418 controls in this case‐control study. The genotyping was done by use of a custom‐by‐design 48‐Plex SNP scan TM Kit. Results: This study found that IGF‐1 gene rs2195239 polymorphism decreased the risk of GC. Stratified analyses suggested that the significant association was shown in the females, non‐smokers, non‐drinkers, and age <60 years groups for GC. In addition, IGF‐1 gene rs2195239 polymorphism correlated with the tumor size, tumor clinical stage, and pathological types for GC patients. Conclusion: To sum up, this study shows that IGF‐1 gene rs2195239 polymorphism is associated with the risk and clinical features of GC patients in this Chinese population.